Comparación de lecturas obtenidas por el reflectómetro de dominio de tiempo con las predicciones del análisis numérico del terreno para el talud de casa de máquinas del Proyecto Hidroeléctrico Chucás - Arguedas-Hernández, Jessica María (Instituto Tecnológico de Costa Rica, 2014)
The present work is to compare the readings obtained by the Reflectometer Time Domain with the predictions of the behavior of the land from numerical analysis in various geotechnical sections of the slope of powerhouse Hydroelectric Project Chucás, what is means from the reflection coefficient data obtained from TDR and displacements obtained from the geotechnical model of the slope and compare those. Two geotechnical models were analyzes, located on both sides of the slope and also two theories were use, first Fallas’s theory and the second Dowding’s theory to determine the displacement from the reflection coefficient. In the geotechnical model displacements up to 70 mm were obtained at critical stages 10 and 12 who were cuts at the foot of the slope, theories showed results of 1.5 mm maximum in the case of Fallas and Dowding values were 9x10 -5 maximum. Then these were compared and the magnitude results were not close values but once you were plotted, the behavior was similar in the critical stages of the construction process, especially in tensile stress
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2014.
Keywords: TDR; Desplazamientos; Coeficiente de reflexión; Esfuerzo cortante; Estabilidad de taludes